The manifestations of persuasive communication in Algerian political discourse Analytical study of the speech of President Abdelmadjid Tebboune to Parliament (25/12/2023) - نورالدين دحمان (International Journal of Social Communication, 2025)
The study aims at identifying the methods of persuasive communication and its argumentative dimension in the speeches of the President Abdelmadjid Tebboune. Through the use of discourse analysis methodology in two levels argument and semantic. With its tools: context analysis and path of argumentation. The study concluded that the political discourse touched on every aspect of the target audience's attention, focusing on the persuasive dimension. He employed mental arguments and emotional grooming to convince the recipient's audience and influence its attitudes political and electoral Behavior. However, the recipient can understand the context of the speech, encrypt its markings and understand its inclusion levels.